The distribution and population structure of Aloe pillansii in South Africa, in relation to climate and elevation - Bolus, Cosman (Plant Conservation Unit (PCU), 2017)
South Africa comprises almost 10% of known plant species and also has the only arid zone "hotspot" defined worldwide, namely the succulent Karoo. Anthropogenic climate change predictions for South Africa suggest rapid climate change in the next 50 years will have adverse effects on its vegetation biomes. This study shows how the aborescent succulent, Aloe pillansii, has a limited distribution due significantly to environmental and climatic variables and therefore it is potentially at risk given anthropogenic climate change predictions. The total South African A. pillansii population investigated is made up of 1202 individuals and is found in the Richtersveld, which is part of the Succulent Karoo. The A. pillansii individuals were sampled in terms of their height and geographical position and then defined into subpopulations by a distance of 2 kms of separation. The sub-populations were then evaluated in terms of their respective environmental and climatic variables acquired from a CCWR database for South Africa using Arc View 3.2. The sub-population size class distributions were also constructed so that population dynamics and recruitment could be investigated. The results show how the A. pillansii sub-populations are limited to a specific environmental and climatic range. The sub-populations group along similar environmental and climatic variables with the healthiest sub-populations found at lower elevation, higher temperatures and higher Potential Evapo-Transpiration. The climatic range of A. pillansii is also evident from the range of its environmental and climatic variables and the associated unhealthy sub-populations that lie on the extremes of this range. Recruitment was found to correlate strongly with the environmental and climatic variables, % winter rainfall and elevation, suggesting it is moisture limited. The evidence found in this study of A. pillansii 's specific environmental and climatic distribution may have negative implications for its future survival and conservation especially with present indications of anthropogenic climate change.